Nickel sulphide mineralization associated with Archean komatiites - Lane, Monica Leonie (Rhodes University, Faculty of Science, Department of Geology, 1992)
The distribution of Archean Nickel sulphide deposits reflects tectonic controls operating during the evolution of the granitoid greenstone terrains. Important deposits of komatiitic-affinity are concentrated within, and adjacent to, younger (âˆ¼2.7 Ga), rift-related greenstone belts (e.g. Canada, Western Australia and Zimababwe). Two important classes of Archean Nickel sulphide deposits exist, formerly known as "Dunitic" and "Peridotitic", these are now referred to as Group I and Group II deposits, based on their characteristic structure and composition. Mineralization varies from massive and matrix to disseminated, and is nearly always concentrated at the base of the host unit. Primary ores have a relatively simple mineralogy, dominated by pyrrhotite-pentlandite-pyrite, and to a lesser degree millerite. Metamorphic grades tend to range from prehnite-pumpellyite facies through to lower and upper amphibolite facies. Genesis of Group I and II deposits is explained by the eruption of komatiites into rift-phase greenstone belts, as channelized flows, which assimilated variable amounts of footwall rocks during emplacement. Sulphide saturation was dependent on the mode of emplacement and, the amount of sulphidic sediments that became assimilated prior to crystallization. This possibly accounts for variations in ore tenor. The Six Mile Deposit (SMD) in Western Australia, is an adcumulate body of the Group IIB-type, exhibiting disseminated mineralization. The ore has been "upgraded" due to hydration and serpentinization. A profound weathering sequence exists, which was subsequently utilized during initial exploration. Exploration techniques has been focused on Western Australia, as it is here that the most innovative ideas have emerged.
Keywords: Nickel sulfide; Geology, Stratigraphic -- Archaean